Accretion Signatures on Massive Young Stellar Objects. Issue Volume 9:Issue S307(2014) (23rd January 2015) - Navarete, F.; Damineli, A.; Barbosa, C. L.; Blum, R. D.
Abstract: We present preliminary results from a survey of molecular H2 (2.12 μm) emission in massive young stellar objects (MYSO) candidates selected from the Red MSX Source survey. We observed 354 MYSO candidates through the H2 S(1) 1-0 transition (2.12 μm) and an adjacent continuum narrow-band filters using the Spartan/SOAR and WIRCam/CFHT cameras. The continuum-subtracted H2 maps were analyzed and extended H2 emission was found in 50% of the sample (178 sources), and 38% of them (66) have polar morphology, suggesting collimated outflows. The polar-like structures are more likely to be driven on radio-quiet sources, indicating that these structures occur during the pre-ultra compact Hii phase. We analyzed the continuum images and found that 54% (191) of the sample displayed extended continuum emission and only 23% (80) were associated to stellar clusters. The extended continuum emission is correlated to the H2 emission and those sources within stellar clusters does display diffuse H2 emission, which may be due to fluorescent H2 emission. These results support the accretion scenario for massive star formation, since the merging of low-mass stars would not produce jet-like structures. Also, the correlation between jet-like structures and radio-quiet sources indicates that higher inflow rates are required to form massive stars in a typical timescale less than 10 5 years.